2008
DOI: 10.1086/588522
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Outflow on the Dynamics of Inflow

Abstract: Both numerical simulations and observations indicate that in an advection-dominated accretion flow most of the accretion material supplied at the outer boundary will not reach the inner boundary. Rather, they are lost via outflow. Previously, the influence of outflow on the dynamics of inflow is taken into account only by adopting a radius-dependent mass accretion rate $\dot{M}=\dot{M}_0 (r/r_{\rm out})^s$ with $s>0$. In this paper, based on a 1.5 dimensional description to the accretion flow, we investigate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 26 publications
(38 reference statements)
4
66
0
Order By: Relevance
“…It was assumed that outflow contributes to loss of mass, angular momentum, and thermal energy from accretion discs. By using the method presented by Bu et al (2009) andXi &Yuan (2008) we consider the discontinuity between mass, momentum (radial and azimuthal components of momentum) and energy outflow and inflow. Also simulations have indicated that the large scale ordered magnetic field exists in the accretion disc and can produce outflow in both cold and hot accretion flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was assumed that outflow contributes to loss of mass, angular momentum, and thermal energy from accretion discs. By using the method presented by Bu et al (2009) andXi &Yuan (2008) we consider the discontinuity between mass, momentum (radial and azimuthal components of momentum) and energy outflow and inflow. Also simulations have indicated that the large scale ordered magnetic field exists in the accretion disc and can produce outflow in both cold and hot accretion flow.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, it is almost impossible to solve the equations directly. We therefore, following Xie & Yuan (2008), we introduce the parameters ζ1 and ζ2 to evaluate radial and angular velocities of outflow in terms of inflow: vr,w = ζ1vr, vϕ,w = ζ2vϕ.…”
Section: Basic Equationsmentioning
confidence: 99%
“…Recent development in observations has shown more and more evidence of outflows in accretion systems, such as Sgr A* (Marrone et al 2006;Xie & Yuan 2008), soft Xray transients (Loeb et al 2001) and quasars with blueshifted absorption lines (e.g., PG1115+80; Chartas et al 2003). Many two-or three-dimensional numerical simulations of accretion disks have also found outflow in their results (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that the initial specific angular momentum of outflow matter is no greater than that of the accreting matter on the disc. Outflow can contribute to the overall equilibrium, provided that there exists some interaction between the outflow and the disc [19].(5) Large-scale magnetic field. Analogous to the MC process, angular momentum can be taken away very efficiently by virtue of some "open" magnetic field lines anchored in the accretion disc in either Poynting or hydromagnetic fluxes, e.g., the BP process [11,[20][21][22].…”
mentioning
confidence: 99%
“…It is noted that the initial specific angular momentum of outflow matter is no greater than that of the accreting matter on the disc. Outflow can contribute to the overall equilibrium, provided that there exists some interaction between the outflow and the disc [19].…”
mentioning
confidence: 99%